2021
DOI: 10.3389/fcomm.2021.728934
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Understandability and Usability of Health Handbooks Commonly Used in Japan

Abstract: Objective: Various types of handbooks that summarize and record health information (health handbooks) have been used in Japan for many years. The purpose of this study was to explore ways to evaluate the understandability and usability of commonly used printed health handbooks in Japan.Methods: An internet search was performed to identify health handbooks used in Japan. The handbooks were then collected, searched, and evaluated for the quality and functionality of the health-information. The overall understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a previous study evaluating handbooks on child care, the CCI scores ranged from 40% to 80% with a median of 67% 24 . In another study evaluating 14 health handbooks published in Japan, the CCI scores ranged from 69% to 100% with a median score of 81.5% 5 . The revised CCI scores for the PQs in the current handbook ranged from 79% to 96%, suggesting that our handbook scores favourably among health handbooks.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In a previous study evaluating handbooks on child care, the CCI scores ranged from 40% to 80% with a median of 67% 24 . In another study evaluating 14 health handbooks published in Japan, the CCI scores ranged from 69% to 100% with a median score of 81.5% 5 . The revised CCI scores for the PQs in the current handbook ranged from 79% to 96%, suggesting that our handbook scores favourably among health handbooks.…”
Section: Discussionmentioning
confidence: 59%
“…However, the health handbooks regarding dementia have not been as effective. A review of 14 health handbooks published in Japan revealed that all three handbooks that focused on dementia scored below average in health literacy owing to poor clarity and usability 5 . Therefore, there is an urgent need to develop an effective handbook for dementia prevention among older adults with MCI.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations